Dietary nutrient intake and meal-related situations among elderly outpatients with chronic obstructive pulmonary disease from respiratory clinics, Malaysia - Yahya, Nor Farahain; Omar, Noraida; Daut, Ummi Nadira; Adznam, Siti Nur’Asyura; Mohd Yusof, Barakatun Nisak (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
Introduction: Chronic obstructive pulmonary disease (COPD) patients usually have dietary problems leading to malnutrition issues. Therefore, this study aimed to determine macro and micronutrient intakes and meal-related situations among outpatients COPD elderly and its adequacy according to their requirements. Methods: 140 patients were included in this cross-sectional study at Respiratory Clinics of Hospital Serdang and Institut Perubatan Respiratori. Socio-demographic and health status data were collected by interviewing patients and reviewing their medical records. A three-day diet history (two-day on weekdays, one day on weekend) was analysed using Nutritionist Pro and compared against their requirements. Meal-related situation was assessed using three open-ended questions that related to food shopping, cooking and eating and analysed using content analysis. Results: Patients were 70±7 years old, 97% male, 59% Malay, 48% had primary education, 75% married, 72% ex-smokers and 54% presented with comorbidities. Majority of them had no episode of exacerbation for the past one year and in moderate stage of the COPD severity. Mean energy intake was 916±221 kcal/day with 98% of them have under-reported their intake. Almost all patients had inadequate macro and micronutrient intake; energy (97%), protein (97%), carbohydrate (86%), fat (99%), vitamin A (95%), C (86%), D (99%) and E (99%). The meal-related situation reported patients had difficulties with food shopping and preparation and problems during mealtime. Conclusion: COPD elderly reported inadequate intake of macro and micronutrients and had problems during mealtime. This indicates the need for Malaysian nutrition guidelines specific to COPD patients and nutrition intervention in the primary setting.